2013
DOI: 10.1097/ico.0b013e31828a8b96
|View full text |Cite
|
Sign up to set email alerts
|

Tear HSV-Specific Secretory IgA as a Potential Indicator for Recurrent Stromal Herpes Simplex Keratitis

Abstract: This is the first preliminary study suggesting that the levels of tear sIgA could be a potential prognostic parameter for the recurrence of HSK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Our previous study tested the tear HSV-sIgA concentrations of 41 stromal HSK and suggested that the levels of tear sIgA could be a potential prognostic parameter for the recurrence of stromal HSK [7]. This present research had enlarged the samples and prolonged the follow-up time, and the results showed that in univariate analysis tear HSV-sIgA, tear HSV-DNA and the episodes were potential risk factors for HSK recurrence.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our previous study tested the tear HSV-sIgA concentrations of 41 stromal HSK and suggested that the levels of tear sIgA could be a potential prognostic parameter for the recurrence of stromal HSK [7]. This present research had enlarged the samples and prolonged the follow-up time, and the results showed that in univariate analysis tear HSV-sIgA, tear HSV-DNA and the episodes were potential risk factors for HSK recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…Tear HSV-sIgA is proved an adjunct to HSK diagnosis [6]. Our previous study has found that tear HSV-sIgA could be a potential prognostic parameter for the recurrence of stromal HSK [7].…”
Section: Introductionmentioning
confidence: 99%
“…In our report, only 1 of the 5 cases was promptly diagnosed with its typical dendritic shape under corneal fluorescent staining. Therefore, an early and accurate diagnosis is very important, for which the tear HSV-sIgA examination can be very useful in diagnosing stromal HSK and predicting recurrence, even for atypical or unsuspected cases [ 11 , 12 ]. Two of our cases were quickly diagnosed with elevated tear HSV-sIgA, and successfully controlled with antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal scrapings were performed in all cases under topical anesthesia and then inoculated directly into primary culture media for bacteria and fungi. Tear samples from the lower fornixes of both eyes were collected and assayed by enzyme-linked immunosorbent assay (ELISA) to detect HSV sIgA [ 12 ]. For cases with negative tear HSV-sIgA, small cornea tissue around the ulcer was scraped and processed for DNA extraction, and then a corneal HSV DNA polymerase chain reaction (PCR), or next-generation metagenomics sequencing (mNGS) test was chosen to detect the HSV pathogen load [ 13 ].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation